The Effect of Nonalcoholic Fatty Liver Disease on Extrahepatic Cancers: Evidence From Population‐Based Cohort and Mendelian Randomization - Wei Wang; Pengfei Sun; Xintian Ren; Tingting Lv; Min Li (Health Science Reports)
ABSTRACT Background and Aims Nonalcoholic fatty liver disease (NAFLD) is an escalating global health concern with significant implications for cancers. A better understanding of the causal relationship between NAFLD and extrahepatic cancers might help in clinical management of NAFLD and prevent its adverse outcomes. Methods This study encompassed two complementary approaches. First, the cross‐sectional analysis was performed to examine the association between NAFLD and extrahepatic cancers, utilizing individual‐level data from the National Health and Nutrition Examination Survey (2017‐March 2020, 2021‐2023 cycles). Logistic regression model was utilized to evaluate the association. Subsequently, Mendelian randomization (MR) analysis was conducted to explore the causal association between NAFLD and extrahepatic cancers. Summary‐level data for genetically predicted NAFLD and extrahepatic cancers were derived from large‐scale genome‐wide association studies (GWAS), IEU Open GWAS project and the UK Biobank. The inverse variance weighting (IVW) method with a random‐effect model was utilized as the main analysis. Results A total of 10,010 participants were included in the cross‐sectional analysis. No association was observed between NAFLD and extrahepatic cancers after adjusting for potential confounders, with odd ratios (ORs) ranging from 0.872 to 2.171. IVW MR analysis showed genetic liability to genetically predicted cALT and imaging‐and‐biopsy confirmed NAFLD were not causally associated with extrahepatic cancers, with ORs ranging from 0.957 to 1.118 (all p > 0.050). Moreover, genetically predicted cALT and imaging‐and‐biopsy confirmed NAFLD were causally associated with liver & bile duct cancer (OR = 1.001, 95% CI = 1.000–1.001, p = 0.011; OR = 1.001, 95% CI = 1.000–1.001, p < 0.001), reinforcing a well‐documented link between NAFLD and liver & bile duct cancer. Conclusion Our findings demonstrated that NAFLD was not causally associated with common extrahepatic cancers. Further research is required to validate these results from a mechanistic perspective.